Photobiomodulation on KATP Channels of Kir6.2-Transfected HEK-293 Cells - Fu-qing Zhong; Yang Li; Xian-qiang Mi (International Journal of Photoenergy)
Background and Objective. ATP-sensitive potassium (KATP) channel couples cell metabolism to excitability. To explore role of KATP channels in cellular photobiomodulation, we designed experiment to study effect of low intensity 808 nm laser irradiation on the activity of membrane KATP channel. Study Design/Materials and Methods. Plasmids encoding Kir6.2 was constructed and heterologously expressed in cultured mammalian HEK-293 cells. The patch-clamp and data acquisition systems were used to record KATP channel current before and after irradiation. A laser beam of Ga-As 808 nm at 5 mW/cm2 was used in experiments. A one-way ANOVA test followed by a post hoc Student-Newman-Keuls test was used to assess the statistical differences between data groups. Results. Obvious openings of KATP channels of Kir6.2-transfected HEK-293 cells and excised patches were recorded during and after low intensity 808 nm laser irradiation. Compared with the channels that did not undergo irradiation, open probability, current amplitude, and dwell time of KATP channels after irradiation improved. Conclusions. Low intensity 808 nm laser irradiation may activate membrane KATP channels of Kir6.2-transfected HEK-293 cells and in excised patches.